Comparative transcriptome analysis reveals that ATP synthases regulate Fusarium oxysporum virulence by modulating sugar transporter gene expressions in tobacco - Gai, Xiaotong; Li, Shuang; Jiang, Ning; Sun, Qian; Xuan, Yuan Hu; Xia, Zhenyuan (Frontiers in Plant Science, 2022)
Fusarium oxysporum is a main causative agent of tobacco root rot, severely affecting tobacco growth. Here, 200 F. oxysporum strains were isolated and examined for their virulence toward tobacco plants. These strains were divided into disease class 1-3 (weak virulence), 4-6 (moderate virulence), and 7-9 (strong virulence). To understand the virulence mechanism of F. oxysporum, a comparative transcriptome study was performed using weak, moderate, and strong virulence-inducing strains. The results showed that expression levels of 1678 tobacco genes were positively correlated with virulence levels, while expression levels of 3558 genes were negatively associated with virulence levels. Interestingly, the expression levels of ATP synthase genes were positively correlated with F. oxysporum virulence. To verify whether ATP synthase gene expression is associated with F. oxysporum virulence, 5 strains each of strong, moderate, and weak virulence-inducing strains were tested using qRT-PCR. The results confirmed that ATP synthase gene expression is positively correlated with virulence levels. Knock-out mutants of ATP synthase genes resulted in a relatively weak virulence compared to wild-type as well as the inhibition of F. oxysporum-mediated suppression of NtSUC4, NtSTP12, NtHEX6, and NtSWEET, suggesting that ATP synthase activity is also associated with the virulence. Taken together, our analyses show that ATP synthases are key genes for the regulation of F. oxysporum virulence and provide important information for understanding the virulence mechanism of F. oxysporum in tobacco root rot.